Peningkatan Kemampuan Membaca Al-Qur’an Pada Lansia Dengan Metode Bagdadi di RT/RW 003/010 Pamulang Permai 1 Kecematan Pamulang Barat - Suhartawan, Budi (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to improve the ability of elderly individuals to read the Qur’an in RT/RW 003/010 Pamulang Permai 1, Pamulang Barat District, South Tangerang, Banten. Many elderly people in the area are unable to read the Qur’an due to limited access to religious education during their youth and cognitive decline in older age. To address this issue, the Bagdadi method was employed, known for its structured and gradual approach to Qur’anic reading instruction. The program was carried out using an action research model consisting of four stages: planning, action, observation-evaluation, and reflection. The results show a significant improvement in participants’ ability to recognize Arabic letters, pronunciation, and basic tajwid rules. Beyond technical improvements, the program also fostered a stronger spiritual connection and increased social engagement among the elderly. This initiative is expected to serve as a model for inclusive and sustainable Qur’an education for senior communities.